CALCIUM EXCHANGES BETWEEN SEDIMENTS AND WATER IN SOME CULTURE PONDS WITH STRESS ON CARBONATE AND BICARBONATE ALKALINITIES - Ramamirtham, C P; Dinesh Babu, A P (Indian Journal of Fisheries, 2011)
Calcium is an essential element whichshould be present in the environment for lifeactivities of organisms. Greenway Peter(1983) stated that marine decapods lose their90% of body calcium during 'ecdysis', andcalcification of new exoskeleton is achievedpredominantly with the cakium absorbedfrom seawater.